1994
DOI: 10.1152/ajpheart.1994.267.3.h1010
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the gating of the cardiac sarcoplasmic reticulum Ca(2+)-release channel by H2O2 and dithiothreitol

Abstract: The effect of hydrogen peroxide (H2O2) on the sheep cardiac sarcoplasmic reticulum (SR) Ca(2+)-release channel has been investigated under voltage-clamp conditions after incorporation of native membrane vesicles into planar phospholipid bilayers. In the presence of micromolar activating calcium concentrations on the cytosolic side of the membrane, H2O2 (3-5 mM) increased open probability of the channels. H2O2 did not affect the conductance of the channel or the response to activating compounds, such as ATP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
87
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 0 publications
8
87
1
Order By: Relevance
“…RyR is an established redox-sensitive channel and alterations in its redox state can result in either activation (Stoyanovsky et al 1997;Eager and Dulhunty 1998) or inactivation (Boraso and Williams 1994;Marengo et al 1998). Other key components of Ca 2þ regulation and E-C coupling, e.g., SERCA and Ca v 's, are also redox modulated.…”
Section: Reactive Oxygen Species and Reactive Nitrogen Speciesmentioning
confidence: 99%
“…RyR is an established redox-sensitive channel and alterations in its redox state can result in either activation (Stoyanovsky et al 1997;Eager and Dulhunty 1998) or inactivation (Boraso and Williams 1994;Marengo et al 1998). Other key components of Ca 2þ regulation and E-C coupling, e.g., SERCA and Ca v 's, are also redox modulated.…”
Section: Reactive Oxygen Species and Reactive Nitrogen Speciesmentioning
confidence: 99%
“…We and other groups have shown in guinea-pig and rat isolated myocytes that these changes are the consequence of intracellular calcium loading (Beresewicz & Horackova, 1991;Cerbai et al, 1991;Jabr & Cole, 1993;Mugelli et al, 1995), possibly involving abnormalities in sarcoplasmic reticulum Ca2+ release (Shattock et al, 1990;Boraso & Williams, 1994). In fact, prolongation of action potential duration and development of early-(EAD) and delayed afterdepolarizations (DAD) are prevented by intracellular EGTA (Cerbai et al, 1991;Jabr & Cole, 1993;Mugelli et al, 1995) and/or by pretreatment of the cells with ryanodine (Beresewics & Horachova, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The channel opens in response to a signal from the transverse tubules, which is triggered by membrane depolarization (2), and the resulting flux of Ca 2ϩ from the sarcoplasmic reticulum initiates the sequence of events that leads to muscle contraction. Several laboratories have clearly demonstrated that the activity of the Ca 2ϩ release channel is modulated by oxidation-reduction reactions (3)(4)(5)(6)(7)(8)(9)(10)(11). Oxidizing agents that stimulate Ca 2ϩ release from the sarcoplasmic reticulum include H 2 O 2 (3), 2,2Ј-dithiodipyridine, 4,4Ј-dithiodipyridine (4), Cu 2ϩ phthalocyanine dyes (5), anthraquinone doxorubicin (6,7), and thimerosal (8).…”
mentioning
confidence: 99%
“…These studies led Abramson and Salama (10) to propose a model for redox modulation of the channel that involves three different sulfhydryl groups that exist in close proximity and that can form mixed disulfides to open or close the channel. The evidence that the channel can be altered by oxidation is conclusive (3)(4)(5)(6)(7)(8)(9)(10)(11); the question is whether this oxidation plays a physiological role in skeletal muscle. It is not yet known if disulfide interchange or oxidation-reduction of sulfhydryls on the Ca 2ϩ release channel contribute to normal excitation-contraction coupling, but an increasing body of evidence suggests that such a mechanism could be an important modulatory element.…”
mentioning
confidence: 99%